2020
DOI: 10.2196/21705
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Remote Home Monitoring of Vital Signs in Patients Discharged Early After Esophagectomy: Observational Feasibility Study

Abstract: Background Hospital stays after major surgery are shorter than ever before. Although enhanced recovery and early discharge have many benefits, some complications will now first manifest themselves in home settings. Remote patient monitoring with wearable sensors in the first days after hospital discharge may capture clinical deterioration earlier but is largely uncharted territory. Objective This study aimed to assess the technical feasibility of patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…An observational study of 20 patients discharged after oesophagostomy showed participants’ use of virtual care with RAM after discharge was feasible and well received by all patients. 8 A study compared 54 orthopaedic surgery patients—who had postoperative home monitoring of blood pressure, heart rate, oxygen saturation, and pain scores four times a day for four days after discharge with specified alert protocols to a healthcare provider—with 107 orthopaedic surgery patients who received standard care after hospital discharge. 3 This observational study reported an 80% relative risk reduction in the composite of hospital readmission and emergency department visit at 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study of 20 patients discharged after oesophagostomy showed participants’ use of virtual care with RAM after discharge was feasible and well received by all patients. 8 A study compared 54 orthopaedic surgery patients—who had postoperative home monitoring of blood pressure, heart rate, oxygen saturation, and pain scores four times a day for four days after discharge with specified alert protocols to a healthcare provider—with 107 orthopaedic surgery patients who received standard care after hospital discharge. 3 This observational study reported an 80% relative risk reduction in the composite of hospital readmission and emergency department visit at 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies that use the surgical patient as a research population. However, these are usually studies which take place in-hospital or in which the patient has been in the hospital for several days between surgery and discharge [27][28][29][30]. Therefore, Some limitations need to be addressed as well.…”
Section: Discussionmentioning
confidence: 99%
“…Leenen et al recently published a systematic review of the literature reporting the feasibility of the use of 13 devices and their validation for in-hospital continuous vital signs monitoring. 18 Since this publication, telemonitoring has been studied outside the hospital either in patients who have undergone esophagectomy during the first 7 days at home after discharge 19 or in patients with COVID-19. 9,20 Some points remain to be clarified, notably the frequency of artefacts and false alarms and the clinical consequences of the use of remote monitoring.…”
Section: Discussionmentioning
confidence: 99%